Fragmentarism as a way of organizing musical texts in the 1970s – 1990s - Siuta, Bogdan O.; Bench, Olga G. (Linguistics and Culture Review, 2021)
The last third of the XX century is marked in the musical work with a search for new scientific and creative paradigms, their change and approbation. Fragmentarism is one of the most important among them, which became actual and primary one at this time for organizing the form and modeling the meaningful levels of musical works. The relevance of the study is conditioned by the fact that the fragmentarism (previously peripheral) in the last third of the XX century becomes a factor in organizing the form and coding of the content of a piece of music. The phenomenon of precedent and intertextuality have become increasingly important in the diversification of content when using these principles, along with methods of mixed style and mixed genre. The purpose of this paper is to identify the role of these factors in the modeling of content in musical works of the last third of the XX century. The leading method to the study of this issue is the analysis method, which allows to comprehensively consider the functional load of precedent phenomena as components of content making in the music of the last third of the XX century.